1984
DOI: 10.1039/dt9840000063
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and supramolecular structures of complexes of BF3NH3 and BH3NH3 with 18-crown-6

Abstract: The macrocyclic polyether 18-crown-6 (C, 2H2406) readily forms crystalline 1 : 1 complexes with the adducts BF3NH3 and BH3NH3. Crystals of the solvates BF3N.H3C,2H2406CH2C12 and BH3NH3C12H2,06*MeOH were suitable for X-ray crystallographic investigation. In both cases, the crystal structures reveal that 18-crown-6 adopts an all-gauche conformation with pseudo D3d symmetry in which the intermolecular N-H * -0 hydrogen-bonding interactions between the macrocyclic polyether and the adducts are associated directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…The gas phase structure of 1 determined using microwave spectroscopy reveals a significantly longer B-N bond distance of 1.6722(5) A ˚.42,43 X-Ray crystal structures of 1 : 1 and 2 : 1 adducts of 1 and crown ethers have shown that the N-H moieties of 1 can participate in hydrogen bonding interactions with electronegative elements 44-49 and the B-N bond has an intermediate distance of 1.604(32) A ˚. 44 The solid state structure of neat 1 exhibits short BH • • • HN intermolecular contacts; the hydridic hydrogen atoms on boron are 2.02 A ˚away from the protic hydrogen atoms on nitrogen of an adjacent molecule, a distance less than the Van der Waals distance of 2.4 A ˚, an interaction constituting a dihydrogen bond. 41,50-52 These dihydrogen bonding interactions in 1 have been observed using Raman spectroscopy 53,54 and investigated theoretically.…”
Section: Preparation and Physical Properties Of Ammonia-borane Aminob...mentioning
confidence: 99%
“…The gas phase structure of 1 determined using microwave spectroscopy reveals a significantly longer B-N bond distance of 1.6722(5) A ˚.42,43 X-Ray crystal structures of 1 : 1 and 2 : 1 adducts of 1 and crown ethers have shown that the N-H moieties of 1 can participate in hydrogen bonding interactions with electronegative elements 44-49 and the B-N bond has an intermediate distance of 1.604(32) A ˚. 44 The solid state structure of neat 1 exhibits short BH • • • HN intermolecular contacts; the hydridic hydrogen atoms on boron are 2.02 A ˚away from the protic hydrogen atoms on nitrogen of an adjacent molecule, a distance less than the Van der Waals distance of 2.4 A ˚, an interaction constituting a dihydrogen bond. 41,50-52 These dihydrogen bonding interactions in 1 have been observed using Raman spectroscopy 53,54 and investigated theoretically.…”
Section: Preparation and Physical Properties Of Ammonia-borane Aminob...mentioning
confidence: 99%
“…[12] 146. [16] According to equation (10) the slope of the plot of ko;: versus c (Co") equals K,/k, c (0,); thus the pressure dependence of the slope arises from the pressure dependence of K , and k , . Fortunately, reaction (7) is diffusion-controlled and k , will therefore vary with pressure in the same way as the viscosity of the solvent.…”
mentioning
confidence: 99%
“…Turning to single crystal X-ray crystallography, crystals from the sublimed product were grown via two different methods and obtained as a glyme solvate and a crown ether adduct. 19 Both structures showed the intermediate to be the branched, cyclic aminoborane tetramer , B-(cyclotriborazanyl)-amine-borane ( 3 , BCTB). ( Fig.…”
Section: Resultsmentioning
confidence: 99%